Efficient light harvesting in hybrid quantum dot–interdigitated back contact solar cells via resonant energy transfer and luminescent downshifting. Issue 40 (9th October 2019) - Krishnan, Chirenjeevi; Mercier, Thomas; Rahman, Tasmiat; Piana, Giacomo; Brossard, Mael; Yagafarov, Timur; To, Alexander; Pollard, Michael E.; Shaw, Peter; Bagnall, Darren M.; Hoex, Bram; Boden, Stuart A.; et al.
Abstract : In this paper, we propose a hybrid quantum dot (QD)/Solar cell configuration to improve the performance of IBC silicon solar cells through efficient utilisation of resonant energy transfer (RET) and luminescent downshifting (LDS). Abstract : In this paper, we propose a hybrid quantum dot (QD)/solar cell configuration to improve performance of interdigitated back contact (IBC) silicon solar cells, resulting in 39.5% relative boost in the short-circuit current ( J SC ) through efficient utilisation of resonant energy transfer (RET) and luminescent downshifting (LDS). A uniform layer of CdSe1− x S x /ZnS quantum dots is deposited onto the AlO x surface passivation layer of the IBC solar cell. QD hybridization is found to cause a broadband improvement in the solar cell external quantum efficiency. Enhancement over the QD absorption wavelength range is shown to result from LDS. This is confirmed by significant boosts in the solar cell internal quantum efficiency (IQE) due to the presence of QDs. Enhancement over the red and near-infrared spectral range is shown to result from the anti-reflection properties of the QD layer coating. A study on the effect of QD layer thickness on solar cell performance was performed and an optimised QD layer thickness was determined. Time-resolved photoluminescence (TRPL) spectroscopy was used to investigate the photoluminescence dynamics of the QD layer as a function of AlO x spacer layer thickness. RET can be evoked between the QD and Si layers for very thin AlO x spacer layers, with RET efficiencies of up to 15%. In the conventional LDS architecture, down-converters are deposited on the surface of an optimised anti-reflection layer, providing relatively narrowband enhancement, whereas the QDs in our hybrid architecture provide optical enhancement over the broadband wavelength range, by simultaneously utilising LDS, RET-mediated carrier injection, and antireflection effects, resulting in up to 40% improvement in the power conversion efficiency (PCE). Low-cost synthesis of QDs and simple device integration provide a cost-effective solution for boosting solar cell performance.